PENGARUH LATIHAN KELINCAHAN TERHADAP HASIL BERMAIN DALAM PERMAINAN HADANG PADA SISWA KELAS V SD NEGERI 2 JAPARA - Dava Nur Ramandika; Dadan Muldan (STKIP Subang, 2025)
This study aims to determine the effect of training using Shuttle Run on the agility of traditional sports hadang in fifth grade elementary school students. In this study the authors used quantitative methods. This study uses an experimental research method using a one group pretest - posttest research design. The data collection method uses measurement tests before and after action, with data analysis involving normality tests, homogeneity tests, and hypothesis testing. The sampling of this study used purposive sampling technique, a sampling technique with certain considerations. In this study the researchers took a sample of 15 students of class v SD Negeri 2 Japara. The obstacle game is considered to be able to help in influencing agility through reflex movements, running, and speed.